PENGELOLAAN ASET TANAH PEMERINTAH DAERAH KOTA KUPANG DALAM PERSPEKTIF KEPASTIAN HUKUM DAN KEMANFAATAN HUKUM - Pauto Wirawan Neno; Kotan Y. Stefanus; Markus Y. Hage (Yayasan Nusantara Hasana Berdikari, 2025)
This study aims to find out the Management of Land Assets Owned by the Kupang City Government; find out the Management of Land Assets of the Kupang City Regional Government from the Perspective of Legal Certainty; find out the Management of Land Assets of the Kupang City Regional Government from the Perspective of Legal Benefits. The type of research conducted is normative legal research (normative legal research method). The normative legal research method is library legal research conducted by examining library materials or secondary data alone. The research results show that (1) Management of regional assets in the form of Kupang City Regional Government Land Assets is carried out based on laws and regulations in three Regulatory Periods, namely: a) Regulation of the Minister of Home Affairs Number 17 of 2007 concerning Technical Guidelines for Management of Regional Property; b) Regulation of the Minister of Home Affairs Number 19 of 2016 concerning Guidelines for Management of Regional Property; and c) Regulation of the Minister of Home Affairs Number 7 of 2024 concerning Amendments to Regulation of the Minister of Home Affairs Number 19 of 2016 concerning Guidelines for Management of Regional Property. (2) From the perspective of legal certainty, the Management of Land Assets of the Kupang City Regional Government has not fully met the value of legal certainty. (3) From the perspective of legal benefits. The Management of Land Assets of the Kupang City Regional Government has not fully met the value of legal benefits.